Optimalisasi Penerangan Jalan Umum (PJU) di Dermaga Pelabuhan Wani 2 dengan Simulasi Dialux Evo - Nawawi, Alfi; Kali, Agustinus; Mahmudi, Irwan; Sholihah, Ratih Mar'atus (SMARTICS Journal, 2025)
The Wani 2 Port Pier, located in Tanantovea District, Donggala Regency, is a vital infrastructure equipped with a Gantry Crane that requires optimal street lighting to support loading and unloading activities as well as maritime and land transportation. This study aims to analyze the lighting intensity and its compliance with the standards set by SNI 7391:2008, the Ministry of Public Works and Public Housing, the Ministry of Maritime Transportation, and the Ministry of Health Regulation No. 70 of 2016, which recommends a minimum illumination level of 20 lux. An evaluation of the existing street lighting system indicates that the average lighting intensity remains below the established standard, ranging from 8 to 16 lux. This discrepancy is attributed to the varying distances between light poles, which range from 15–20.5 meters and the use of 100-watt LED lamps with an output of 12,500 lumens and a color temperature of 4000 Kelvin, which are not optimal. To address this issue, this study optimizes the street lighting system through simulations conducted using DIALux Evo software. The proposed improvements include modifying the lamp specifications and increasing the number of lamps. This upgrade results in a total luminous output of 30,000 lumens. Additionally, adding one streetlight with a 14-meters spacing between poles enhances overall illumination. The simulation results indicate that modifying the lamp specifications and adding streetlight points significantly improve light distribution. The achieved illumination levels comply with SNI 7391:2008 and the Ministry of Health Regulation No. 70 of 2016.